Self-Regulated Learning Strategy in Conducting Remote Lecturing During Covid-19 Pandemic - Adam, Nurul Suciana; Kartowagiran, Badrun; Yansa, Hajra; Marlina, Marlina; Amiruddin, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Since the outbreak of the COVID-19 virus hit Indonesia, the Work from Home Policy of working, studying, and worshiping at home has been implemented to reduce community activities outside the home. To maintain students’ academic performance in remote lecturing during the COVID-19 Pandemic, it needed a strategy to plan, monitor, and evaluate academic progress. The study aimed to investigate the Self-Regulated Learning (SRL) strategy in remote lecturing. The research design used was a survey method with a quantitative approach. The subjects of this study numbered 209 higher university students by using the convenience sampling technique. The data collection technique used was the SRL scale developed by Zimmerman. The scale was inputted into Google Form, then distributed online. The Aiken index validity and reliability using Cronbach Alpha showed good validity and high reliability. The data analysis techniques were descriptive statistics, MANOVA and ANOVA. The findings showed that the Self-Control indicator was the most dominant factor among students. Besides, there was no significant difference simultaneously between men and women and inconclusive results related to gender in SRL in the distance lecturing implementation.